2006
DOI: 10.1080/13625180500361058
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone medical abortion in Albania: Results from a pilot clinical research study

Abstract: A reduced dose mifepristone medical abortion regimen with home administration of misoprostol is feasible for introduction into healthcare facilities in Albania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The ORs for complete abortion at home versus in a clinic showed no difference in effectiveness in five studies. 9,24,25,28,29 In three studies (two French, 26,31 one Vietnamese) 30 medical abortion in clinic settings was found to be more effective, while in the study conducted in both Tunisia and Viet Nam abortion at home proved more effective (OR: 2.9; 95% CI:…”
Section: Complete Abortionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ORs for complete abortion at home versus in a clinic showed no difference in effectiveness in five studies. 9,24,25,28,29 In three studies (two French, 26,31 one Vietnamese) 30 medical abortion in clinic settings was found to be more effective, while in the study conducted in both Tunisia and Viet Nam abortion at home proved more effective (OR: 2.9; 95% CI:…”
Section: Complete Abortionmentioning
confidence: 99%
“…24 The average success rate in this group was 89.7% (95% CI: 88.7-90.7%) ( Table 2). Among the 1044 women who took misoprostol in clinic, the success rate ranged from 80% in Turkey 9 to 99% in France.…”
Section: Complete Abortionmentioning
confidence: 99%
See 3 more Smart Citations